2014
DOI: 10.3928/21650799-20140305-02
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Obesity Among Employees of a Manufacturing Plant: Translating the Diabetes Prevention Program to the Workplace

Abstract: Obesity affects individuals physically and emotionally, contributing to direct and indirect employer costs. Targeted obesity interventions through the Diabetes Prevention Program Lifestyle Core Curriculum offered at the worksite could promote healthy lifestyle decisions resulting in weight improvement among overweight and obese employees. A pretest-posttest cohort design was used to evaluate changes in weight and body mass index among 35 Diabetes Prevention Program participants; they achieved statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Although the worksite holds promise for successful delivery of DPP-like behavioral lifestyle intervention, such programs have not been extensively examined in this setting (41-45). …”
Section: Introductionmentioning
confidence: 99%
“…Although the worksite holds promise for successful delivery of DPP-like behavioral lifestyle intervention, such programs have not been extensively examined in this setting (41-45). …”
Section: Introductionmentioning
confidence: 99%
“…For example, a construction worker must lift heavy objects, while a white-collared employee may spend majority of his or her working hours at a desk. Considering the amount of time and money obesity in the workplace has cost, companies have targeted their focus on developing interventions that are tailored to different occupational settings [33,35,37,39,40]. In turn, employees often know what makes a workplace vibrant.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of obesity prevention or weight management intervention programs and strategies in the workplace, in a form of health promotion or worker wellness programs aimed at weight, nutrition, stress, and physical activity, taking into consideration the obesity rates of today, may be important for employers to consider [33][34][35][36][37][38][39][40] ( Table 2 [42]. In a recent literature review of the effectiveness of workplace health interventions by Schröer et al, beneficial health effects have been found in interventions aimed at workplace nutrition and multi-component physical activity, both of which, when combined, showed a greater effect on weight loss over solely one or the other; however, this review have not found any evidence of increased efficacy associated with any specific intervention reviewed [43].…”
Section: Obesity and Interventionsmentioning
confidence: 99%
“…NCD have been associated with increased out of pocket expenditure in India, 19,45 with chronic conditions like diabetes reported to be associated with increased sick absenteeism, physical and mental disability, decreased productivity for employees, and greater expenditure and hence economic impact for employers. 13,46,47 Even low intensity of active workplace interventions have been associated with healthy dietary habits, increase physical activity participation, improved blood pressure control and improve awareness and knowledge, 12,13 apart from reducing time, cost and travel barrier. 13 The current study is limited by retrospective study design with sampling bias, temporal ambiguity and sample heterogeneity restricting generalizability.…”
mentioning
confidence: 99%
“…13,46,47 Even low intensity of active workplace interventions have been associated with healthy dietary habits, increase physical activity participation, improved blood pressure control and improve awareness and knowledge, 12,13 apart from reducing time, cost and travel barrier. 13 The current study is limited by retrospective study design with sampling bias, temporal ambiguity and sample heterogeneity restricting generalizability. The self-reporting nature of the disease add on to reporting bias leading to over or under estimation of the prevalence.…”
mentioning
confidence: 99%